PEMBELAJARAN PEMBUATAN DIAGRAM BUNGA DAN RUMUS BUNGA UNTUK MENGIDENTIFIKASI TUMBUHAN - Dece Elisabeth Sahertian; Efraim Samson; Sanita Suriani (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Morphology is the science that studies the external characteristics of plants. Plant characteristics are the most important part in identifying unknown plants. Plant characteristics used in identification are leaf organs, stems, roots, flowers, fruits and seeds. Flowers are one part that can be used as a sample to identify a flower in a taxa order, family or genus. There are two ways to identify plants, namely by using floral diagrams and floral formulas. The purpose of this activity is to provide knowledge about plant identification material and plant morphology, especially identification of plants based on the morphological characteristics of flowers by illustrating flower diagrams and compiling a flower formula for a plant. This activity was given to students of SMA Negeri 7 Leihitu and SMA Negeri 1 TNS. The stages of the activity are the initial approach with the school principal regarding permission to carry out Community Service activities in the school he leads. Then delivering material on flower morphology related to identifying plants, introductory material on floral diagrams and floral formulas, preparing tools and materials, training students with several examples of questions and practice. The community service activities were carried out well, safely, smoothly, and successfully. The activity of introducing and identifying the types of flowering plants around the school through making flower diagrams and compiling flower formulas, was attended by students with feelings of joy, curiosity and enthusiasm. This can be seen from the practical results displayed by each group which demonstrates qualified science skills. Each group is considered capable of making flower diagrams and compiling flower formulas based on the flower structure of each flower.